Reactive P/S/N-containing synergistic flame retardant towards eco-friendly durable flame-retardant cotton fabric: Flame-retardant property, durability and mechanism. (15th January 2023) - Tu, Jiang; Xie, Suhui; Zhao, Qianyu; Guan, Jinping; Wu, Chunhong; Wang, Peng
Abstract: Developing eco-friendly durable flame-retardant cotton fabric not only expands its application area, but also caters to the healthy and environmentally friendly concept of consumers. Herein, a reactive P/S/N-containing synergistic flame retardant (PSN) was synthesized to prepare eco-friendly durable flame-retardant cotton fabric through chemical modifying method. Flame-retardant finishing deteriorated the softness, whiteness, tensile strength and air permeability of cotton fabric. PSN conferred outstanding flame retardancy, fire safety and durability to cotton fabric. For treated fabric with the add-on of 14.2%, it achieved an LOI value of 36.5% and extinguished spontaneously even after 50 laundering cycles. Its peak heat release rate, total heat release and fire growth rate index values decreased sharply than those of the control fabric. PSN exhibited high-efficiency flame-retardant behavior, and the synergy between P, S and N elements facilitated the formation of intumescent barrier on the fiber surface during combustion. The hydrolysis of covalent bond and formation of phosphate/sulphonate during laundering both accounted for the decrease in flame retardancy of treated fabric. Highlights: A reactive P/S/N-containing synergistic flame retardant (PSN) was synthesized. PSN conferred outstanding flame retardancy, fire safety and durability to cotton fabric. PSN showed high flame-retardant activity because of phosphorus-sulfur-nitrogen synergy.